A computer-generated plus-shaped arrangement and its architectural applications. Issue 4 (1st June 2017) - Shekhawat, Krishnendra
Graphical abstract: Abstract: This work consider the problem of rectilinear arrangement which is about arranging given rectangular objects of different sizes in the frame of a given rectilinear polygon while considering dimension and position of each rectangle and adjacency relations among the rectangles. The current work is part of a larger work aimed at automated generation of rectilinear arrangements while satisfying given dimensional and topological constraints. In this paper, we present a set of algorithms for obtaining a plus-shaped arrangement. In addition, we present some heuristic techniques for reducing the size of extra spaces present inside the obtained arrangement. At the end, we demonstrate architectural application of the presented work.